Teachers' explicit expectations and implicit prejudiced attitudes to educational achievement: Relations with student achievement and the ethnic achievement gap. (April 2016) - Peterson, E.R.; Rubie-Davies, C.; Osborne, D.; Sibley, C.
Abstract: In this paper, we consider whether teachers' explicit and implicit prejudiced attitudes underlie the ethnic achievement gap. To date, most research on teacher expectation effects has relied on explicit expectation measures that are prone to social desirability biases. In contrast, we examine the effects of teachers' (a) explicit ethnicity-based expectations for academic achievement and (b) implicit prejudiced attitudes about academic achievement on students' actual academic success over time. A total of 38 teachers completed both a traditional teacher expectation measure and a modified Implicit Association Task designed to assess ethnic stereotypes associated with academic achievement and failure. A multi-level analytic framework showed that students in classrooms of teachers with high expectations performed better in reading at the end of the year and that these effects were found across all ethnic groups. In contrast, whereas students' mathematics achievement scores were largely unrelated to teachers' explicit expectations, teachers' implicit prejudiced attitudes predicted student performance. Specifically, students benefited most academically when their teachers' implicit biases favored the ethnic group to which the student belonged. Findings are discussed in relation to differences in the salience of teachers' expectations and implicit prejudiced attitude in the classroom, and the ethnic achievement gap. Highlights: Teachers' explicit expectations relate to students' year-end reading scores. Teachers' explicit expectations did not vary according to a students' ethnic group. Teachers' implicit prejudiced attitudes relate to students' year-end Math's scores. Some students achieve more when a teachers' implicit prejudice favors their ethnicity.